Development as resistance and translation: Remaking norms and ideas of the Gates Foundation. (April 2018) - Fejerskov, Adam Moe
This article explores how ideas and practices manifested in a Bill and Melinda Gates Foundation-funded project on women's access to land are continuously remade and transformed as they move through the many layers towards implementation. The article builds a theoretical framework that lets us understand development projects as systems of continuous meaning negotiation and translation. It then discusses the particular project's three dominant reconfigurations of gender and women—from instrumentalizing, to legal-institutional, to transformative and deeply political understandings of the project—as it is continuously remade on its way from headquarter and towards implementation in the Indian state of Odisha.